Neuronal Intranuclear Inclusion Disease Without Polyglutamine Inclusions in a Child - McFadden, Kathryn (2005)
Neuronal intranuclear inclusion disease (NIID) is a rare and heterogeneous group of slowly progressive neurodegenerative disorders characterized by the widespread presence of eosinophilic neuronal intranuclear inclusions (NII) accompanied by a more restricted pattern of neuronal loss. We report here the pathologic findings in a 13-year-old boy who died after a 6-year clinical history of progressive ataxia, extrapyramidal manifestations, and lower motor neuron abnormalities. Histological evaluation of the brain revealed widespread NII in most neurons. Marked loss of cerebellar Purkinje cells and neurons in the dentate nucleus, red nucleus, and spinal cord anterior horns was accompanied by a modest astrocytosis. Because of the abundance of NII and the absence of a relationship between NII and neuronal loss or microglial activation, we conclude that loss of cerebellar, brainstem, and spinal cord neurons reflects selective neuronal vulnerability. NII were immunoreactive for ubiquitin, glucocorticoid receptor, and SUMO-1, a small, ubiquitin-like protein purportedly involved in protein transport and gene transcription. NII were non-reactive for polyglutamine (1C2), TATA binding protein, promyelocytic leukemia protein, heat shock protein 90, tau, alpha-synuclein, neurofilament, and beta amyloid. The moderate ubiquitin and strong SUMO-1 staining of NII in juvenile cases is the reverse of the pattern noted in adult diseases, suggesting the two age groups are pathogenically distinct. We suggest that juvenile NIID is a spinocerebellar brainstem ataxic disease possibly related to an abnormality in SUMOylation.